Principles of Honesty in Business according to the Qur'an (Case Study of Cocoa Seed Traders in Cendana Village) - Erni; Abdul Matin Bin Salman (Penerbit Hellow Pustaka, 2024)
This research explores the concept of honesty in a more specific business context, namely in the case study of Cendana Village cocoa seed traders and explores the relevance of the importance of the principle of honesty in the Koran. Cendana Village is a clear example where Islamic principles, including honesty, are implemented in community life and economic activity, with special emphasis on verses that specifically underline honesty in a business context. The research method used is qualitative with a descriptive analysis approach. Primary data was obtained through direct interviews with Cendana Village cocoa seed traders, secondary data was collected through various sources, including library literature related to business, ethics and Islamic principles, as well as print and electronic media which contained articles related to the cocoa business and the principles of honesty in Islam. Cendana Village cocoa seed traders run their business with integrity, transparency and commitment to customer interests and long-term business sustainability. Thus, these traders become a good example for other business practitioners in applying the principle of honesty in their activities. Traders understand that honesty is not only a moral value, but also a solid foundation for building good relationships with customers and ensuring long-term business success.